إرساء فنيات علم النفس الإيجابي لتحسين جودة حياة المعاق حركياً - راشدي,إيمان (University of Eloued جامعة الوادي, 2024)
Abstract : The study aimed to test the techniques of positive psychology, which are: the art of narration, refutation, self-efficacy, positive thinking, gratitude, happiness, flow, optimism, hope, fun and humor to improving the quality of life of the physically disabled. Relying on the clinical approach and its tools represented by the clinical interview, clinical observation, and the brief quality of life scale issued by the World Health Organization, the Arabization and standardization of Hamza Fatima (2018) on sample from the Algerian environment, in addition to the therapeutic protocol based on the previously mentioned positive psychology techniques that were applied. In two cases of the female gender, the results of the study concluded in a positive contribution to taking care of these cases, by improving their quality of life in terms of satisfaction, acceptance, and having a positive concept about themselves and their lives. ملخص : هدفت الدراسة إلى اختبار فنيات علم النفس الإيجابي المتمثلة في: فنية السرد، فنية الدحض، فنية الكفاءة الذاتِية، فنية التفكِير الإيجابي، فنية الاِمتنان، فنية السعادة، فنية التدفُق، فنية التفاؤُل، فنية الأمل، فنية المرح والفكاهة في تحسِين جودة حياة المعاق حركِياً. بالاِعتمادُ على المنهج العِيادِي وأدواته المتمثلة في المقابلة العِيادِية، الملاحظة العِيادِية، مِقياس جودة الحياة المختصر الصادِر عن مُنظمة الصِحة العالمية تعرِيب وتقنين حمزة فاطيمة (2018) على عيِنات من البيئة الجزائِرية، بالإضافة إلى البروتوكول العلاجي المبني على فنِيات عِلم النفس الإيجابي سابِقة الذِكر والتي طبقت على حالتين من جِنس المؤنث، أسفرت نتائِج الدِراسة إلى المساهمة الإيجابية للتكفل بهذه الحالتين، وذلِك من خِلال تحسِين جودة حياتهما من رِضا وتقبُل واِمتِلاك مفهُوم إيجابي عن ذاتِهما وحياتِهما.
Keywords: فنيات علم النفس اإليجابي; جودة الحياة; لمعاق حركيا ً; positive psychology techniques; quality of life; the physically disabled